Low-gas-production positive electrode material as well as preparation method and application thereof
By covering the perovskite composite metal oxides on the positive electrode material of the lithium battery, the problem of gas production in the positive electrode material of the lithium battery is solved, which significantly improves gas production and cycle life, and improves the lithium battery's Safety and battery life.
Patent Information
- Application Number
- CN202411229371.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-20
AI Technical Summary
The existing lithium battery positive electrode materials are prone to side reactions with the electrolyte during use or under harsh conditions to produce gas, resulting in reduced safety and impact on endurance performance. Traditional wrapping technology cannot effectively improve gas resistance.
A composite metal oxide coating layer, specifically a perovskite compound ABO3, is coated on the surface of the matrix particles of the positive electrode material, and uniformly wrapped through hydrothermal reaction and calcination treatment, reducing oxygen evolution overpotential and reducing gas generation.
It significantly improves the gas production and cycle endurance performance of the cathode material of lithium battery, reduces Li consumption, maintains high circulation capacity, and improves the safety and battery endurance of lithium batteries.
Smart Images

Figure CN119170764A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium ion battery materials, and in particular relates to a low gas generation positive electrode material and a preparation method and application thereof. Background Art
[0002] In recent years, with the popularization of household electric cars, mobile phones, drones and other products, people's lives are getting closer and closer to lithium batteries, and with it comes higher requirements for the safety of lithium batteries. At present, the most important issue about lithium battery products is the gas production caused by the side reaction between the surface of the positive electrode material and the electrolyte during use or under harsh conditions. Severe gas production will directly affect the safety of the lithium battery, and will bring about a large capacity loss and impedance increase, thereby affecting the endurance performance of the lithium battery. In addition, encapsulation technology is often used in the prior art to reduce the contact between the positive electrode material and the electrolyte, but the commonly used ball milling mixing and dry sintering methods form larger particles, which cannot exert the coating effect of the material, and thus cannot significantly improve the anti-gassing performance of the positive electrode material in lithium battery applications. Therefore, it is key to find a lithium battery positive electrode material with excellent anti-gassing performance to meet the development needs of lithium batteries. Summary of the invention
[0003] One of the purposes of the present invention is to provide a low gas generation positive electrode material to address the shortcomings of the positive electrode material prepared by the prior art that cannot significantly improve the anti-gas generation performance, which has excellent anti-gas generation performance and good cycle endurance performance and can meet the development needs of lithium batteries.
[0004] Specifically, the low gas generation positive electrode material comprises a positive electrode material matrix particle and a composite metal oxide coating layer wrapped on the surface of the positive electrode material matrix particle; the oxygen evolution overpotential of the lithium battery positive electrode material is ≤0.4V; the composite metal oxide in the composite metal oxide coating layer is a perovskite compound with the general chemical formula ABO3, wherein the A element is a rare earth or alkaline earth metal element, and the B element is a transition metal element.
[0005] In a preferred embodiment, the positive electrode material matrix particles are selected from at least one of lithium cobalt oxide positive electrode material matrix particles, lithium iron phosphate positive electrode material matrix particles, nickel cobalt manganese positive electrode material matrix particles and nickel cobalt aluminum positive electrode material matrix particles.
[0006] In a preferred embodiment, based on the total mass of the low gas generating positive electrode material, the content of the composite metal oxide ABO3 is 0.5-1.5 wt%.
[0007] The second object of the present invention is to provide a method for preparing the above-mentioned low gas-generating positive electrode material, which comprises the following steps: subjecting the positive electrode material matrix particles to a hydrothermal reaction with a coating liquid, wherein the coating liquid contains element A, element B and chitosan, and then calcining the obtained hydrothermal reaction product in an oxygen-containing atmosphere to obtain a lithium battery positive electrode material.
[0008] In a preferred embodiment, the coating liquid is prepared according to the following method: metal salt I containing element A and metal salt II containing element B are added to deionized water to form solution 1, chitosan is evenly mixed with an organic solvent to obtain solution 2, and solution 1 and solution 2 are mixed to obtain the coating liquid.
[0009] In a preferred embodiment, the molar ratio of element A to element B in the solution 1 is 1:(0.5-1.5).
[0010] In a preferred embodiment, the concentration of element A in the solution 1 is 0.8-1.2 mol / L.
[0011] In a preferred embodiment, the concentration of element B in the solution 1 is 0.8-1.2 mol / L.
[0012] In a preferred embodiment, the concentration of chitosan in the solution 2 is 0.1-0.5 g / mL.
[0013] In a preferred embodiment, the volume ratio of solution 1 to solution 2 is (25-45):1.
[0014] In a preferred embodiment, the metal salt I and the metal salt II are each independently selected from at least one of sulfate, nitrate, acetate, oxalate and chloride.
[0015] In a preferred embodiment, the A element is at least one of La, Pr, Gd, Tb, Ca, and Sr.
[0016] In a preferred embodiment, the B element is at least one of Co, Mn, Fe and Ni.
[0017] In a preferred embodiment, the temperature of the hydrothermal reaction is 110-170° C., and the time is 6-20 hours.
[0018] In a preferred embodiment, the calcination treatment is carried out at a temperature of 700-1100° C. and for a time of 4-12 hours.
[0019] The third object of the present invention is to provide a low gas generation positive electrode material prepared by the above method.
[0020] A fourth object of the present invention is to provide application of the above-mentioned low gas generating positive electrode material in lithium ion batteries.
[0021] After extensive and in-depth research, the inventors of the present invention found that coating different coating materials on the surface of the positive electrode material will have a significant impact on the gas production of the positive electrode material during the cycle process. Among them, the material with a lower oxygen evolution overpotential has a stronger oxygen atom binding ability. When the positive electrode material is wrapped with this material as a coating agent, it can bind and fix oxygen atoms on the surface of the coating layer, thereby constructing an oxygen atom buffer layer on the surface, hindering the transport of oxygen atoms in the coating layer and reducing gas generation.
[0022] The key to the present invention is to coat the surface of the positive electrode material matrix particles with a perovskite ABO3 type composite metal oxide, and at the same time, through a method combining a hydrothermal reaction and a calcination treatment, the composite metal oxide can be evenly coated on the surface of the positive electrode material, thereby obtaining a lithium battery positive electrode material with an oxygen evolution overpotential η≤0.4V, which can not only reduce the gas generation during the cycle, but also reduce the consumption of Li due to the less SEI film generated, so that the capacity retention rate of the cycle can be maintained at a high level. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The SEM and EDS images of the positive electrode material prepared in Example 1 are shown in FIG. Figure 1 (1) is the SEM image. Figure 1 (2) is the EDS diagram of La element. Figure 1 (3) is the EDS diagram of Co element.
[0024] Figure 2 It is the oxygen evolution overpotential curve of the positive electrode materials prepared in Example 1 and Comparative Examples 1 and 2.
[0025] Figure 3 This is the XRD pattern of the composite metal oxide LaCoO3 in Example 1. DETAILED DESCRIPTION
[0026] The low gas generation positive electrode material provided by the present invention comprises a positive electrode material matrix particle and a composite metal oxide coating layer wrapped on the surface of the positive electrode material matrix particle; the oxygen evolution overpotential of the lithium battery positive electrode material is ≤0.4V; the chemical formula of the composite metal oxide in the composite metal oxide coating layer is ABO3, wherein the A element is a rare earth or alkaline earth metal element, and the B element is a transition metal element. The alkaline earth metal element is selected from at least one of the ⅡA elements, preferably Ca and / or Sr; the rare earth element is selected from at least one of Sc, Y, and lanthanide metals, preferably at least one of La, Pr, Gd, and Tb. The transition metal element is preferably at least one of Co, Mn, Fe, Cr, Ni, Cu, and Zn, and more preferably at least one of Co, Mn, Fe, and Ni.
[0027] In the present invention, the positive electrode material matrix particles are preferably at least one of lithium cobalt oxide positive electrode material matrix particles, lithium iron phosphate positive electrode material matrix particles, nickel cobalt manganese positive electrode material matrix particles and nickel cobalt aluminum positive electrode material matrix particles. The positive electrode material matrix particles can be purchased or prepared by various existing methods.
[0028] In the present invention, based on the total mass of the low gas generating positive electrode material, the content of the composite metal oxide ABO3 is preferably 0.5-1.5wt%, such as 0.5wt%, 0.8wt%, 1.0wt%, 1.2wt%, 1.5wt% or any value therebetween. Controlling the total content of the A element and the B element in the composite metal oxide coating layer within the above preferred range is more conducive to uniformly wrapping the composite metal oxide on the surface of the positive electrode material matrix particles, thereby being more conducive to reducing the oxygen evolution overpotential of the lithium battery positive electrode material and improving the cycle performance of the lithium battery.
[0029] In the present invention, the preparation method of the low gas generation positive electrode material comprises: subjecting the positive electrode material matrix particles to a hydrothermal reaction with a coating liquid, wherein the coating liquid contains element A, element B and chitosan, and then calcining the obtained hydrothermal reaction product in an oxygen-containing atmosphere to obtain a lithium battery positive electrode material.
[0030] In a preferred embodiment, the preparation method may include the following steps:
[0031] S1, adding metal salt I containing element A and metal salt II containing element B into deionized water to form solution 1, mixing chitosan and an organic solvent evenly to obtain solution 2, and then mixing solution 1 and solution 2 to obtain a coating solution;
[0032] S2, mixing the positive electrode material matrix particles with the coating liquid and performing a hydrothermal reaction, and filtering and drying to obtain a hydrothermal reaction product;
[0033] S3, calcining the hydrothermal reaction product obtained in step S2 in an oxygen-containing atmosphere to obtain a positive electrode material for a lithium battery.
[0034] In the present invention, the molar ratio of element A to element B in the solution 1 is preferably 1:(0.5-1.5), and the molar amount of element A is 1 mol, and the molar amount of element B is preferably 0.5-1.5 mol, such as 0.5 mol, 0.8 mol, 1.0 mol, 1.2 mol, 1.5 mol or any value therebetween. The concentration of element A in the solution 1 is preferably 0.8-1.2 mol / L, such as 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L or any value therebetween. The concentration of element B in the solution 1 is preferably 0.8-1.2 mol / L, such as 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L or any value therebetween. The present invention does not specifically limit the types of metal salts I and II, as long as they are compounds that can be dissolved in water so that element A and element B exist in ionic form. The metal salt I and the metal salt II are each independently selected from at least one of sulfate, nitrate, acetate, oxalate and chloride.
[0035] In the present invention, the concentration of chitosan in the solution 2 is preferably 0.1-0.5 g / mL, such as 0.1 g / mL, 0.2 g / mL, 0.3 g / mL, 0.4 g / mL, 0.5 g / mL or any value therebetween. The volume ratio of the solution 1 to the solution 2 is preferably (25-45):1, such as 25:1, 30:1, 35:1, 40:1, 45:1 or any value therebetween.
[0036] The present invention does not specifically limit the type of organic solvent, as long as the chitosan added to the organic solvent can be completely dissolved. Specifically, the organic solvent can be preferably at least one selected from acetone, methanol, ethanol, isopropanol, ethylene glycol, triethanolamine, cyclohexanone, benzene, toluene, xylene and chlorobenzene.
[0037] In the present invention, the conditions of the hydrothermal reaction include a temperature preferably of 110 to 170°C, such as 110°C, 130°C, 140°C, 150°C, 160°C, 170°C or any value therebetween; and a time preferably of 6 to 20h, such as 6h, 8h, 10h, 12h, 15h, 18h, 20h or any value therebetween.
[0038] In the present invention, the calcination treatment conditions include a temperature of preferably 700-1100°C, such as 700°C, 720°C, 750°C, 780°C, 800°C, 820°C, 850°C, 880°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C or any value therebetween; and a time of preferably 4-12h, such as 4h, 6h, 8h, 10h, 12h or any value therebetween.
[0039] In the present invention, in step S2, the mixing method of the positive electrode material matrix particles and the solution C can be ultrasonic treatment, stirring or other mixing methods. The filtering and drying method can be specifically to filter the hydrothermal reaction product and dry it in a vacuum oven to obtain an intermediate product. Deionized water can be added during the filtration process for multiple filtration and washing, the purpose of which is to remove the metal cation lanthanum and metal cation aluminum in the original solution that are not successfully wrapped on the positive electrode material matrix particles. Among them, the vacuum drying conditions include a temperature of preferably 100 to 120°C and a time of preferably 6 to 12 hours.
[0040] In a specific embodiment, the method for preparing the low gas generation positive electrode material may include the following steps:
[0041] S1, dissolving a metal salt I containing element A and a metal salt II containing element B in deionized water to form a solution 1, so that the concentrations of element A and element B in solution 1 are independently 0.8-1.2 mol / L, dissolving chitosan in an organic solvent to obtain a solution 2, and then mixing solution 1 and solution 2 by stirring or ultrasonic treatment to obtain a coating solution;
[0042] S2, mixing the positive electrode material matrix particles and the coating liquid by stirring or ultrasonic treatment, and then performing a hydrothermal reaction at 110-170° C. for 6-20 hours, filtering the obtained hydrothermal reaction product, and vacuum drying it at 100-120° C. for 6-12 hours to obtain an intermediate product;
[0043] S3, calcining the intermediate product obtained in step S2 in an oxygen-containing atmosphere at 700-1100° C. for 4-12 hours to obtain a positive electrode material for a lithium battery. The oxygen-containing atmosphere is preferably an air atmosphere.
[0044] It should be noted that the terms "Ⅰ" and "Ⅱ" are only used to refer to metal salts in different orders of appearance for easy distinction, and have no other special meanings or limitations on the types of metals. Similarly, the numbers "1" and "2" in "solution 1" and "solution 2" are only used to refer to solutions in different orders of appearance, and have no other special meanings or limitations on the types of solutions and their components.
[0045] In the present invention, the oxygen evolution overpotential η can be obtained by testing using various methods in the prior art, preferably by loading the positive electrode material of a lithium battery on a test electrode for electrochemical testing. The loading method of the positive electrode material of a lithium battery comprises the following steps:
[0046] S1. Dispersing the positive electrode material of a lithium battery in a mixed solution of deionized water, isopropanol and Nafion solution, and obtaining a dispersion after ultrasonic treatment, wherein 1 mg of the positive electrode material is dissolved in 0.08 to 0.2 mL of the mixed solution;
[0047] S2. Drop the dispersion obtained in step S1 onto the glassy carbon electrode and dry it to obtain a load test electrode.
[0048] In the present invention, the amount of isopropanol is preferably 5-40% by volume of deionized water, such as 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or any value therebetween. The amount of Nafion solution is preferably 0.8-2% by volume of deionized water, such as 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2% or any value therebetween.
[0049] The present invention will be described in detail below through specific embodiments.
[0050] Example 1
[0051] S1, dissolving lanthanum chloride and cobalt chloride in a molar ratio of lanthanum ion to cobalt ion of 1:1 in 70 mL of deionized water to form solution 1, so that the concentrations of lanthanum element and cobalt element in solution 1 are both 1 mol / L, dissolving 0.3 g of chitosan in 2 mL of acetone to obtain solution 2, and then mixing solution 1 and solution 2 by stirring to obtain a coating solution;
[0052] S2, mixing 25 g of lithium cobalt oxide positive electrode material matrix particles with the coating liquid by stirring, and then performing a hydrothermal reaction at 150° C. for 10 h, filtering the obtained hydrothermal reaction product, and vacuum drying it at 120° C. for 6 h to obtain an intermediate product;
[0053] S3. The intermediate product obtained in step S2 is calcined in an oxygen-containing atmosphere at 850° C. for 8 hours to obtain a lithium battery positive electrode material, which includes positive electrode material matrix particles and a composite metal oxide coating layer wrapped on the surface of the positive electrode material matrix particles.
[0054] from Figure 3 From the XRD characterization results, it can be seen that the lithium battery positive electrode material prepared in this example has characteristic peaks of LaCoO3 and LiCoO2 (lithium cobalt oxide), indicating that the perovskite-type composite metal oxide LaCoO3 is successfully synthesized and coated on the surface of the positive electrode material. From the EDS characterization, it can be seen that Figure 1 As shown, lanthanum and cobalt are evenly distributed on the surface of the lithium cobalt oxide positive electrode material, that is, LaCoO3 is evenly coated on the surface of the positive electrode material, wherein the content of LaCoO3 is 0.72wt%. The oxygen evolution overpotential curve of the lithium battery positive electrode material prepared in this embodiment is as shown in Figure 2 As shown, its oxygen evolution overpotential η is lower than the values of Comparative Examples 1 and 2.
[0055] Example 2
[0056] S1, dissolving lanthanum nitrate and cobalt nitrate in a molar ratio of lanthanum ion to cobalt ion of 1:0.7 in 70 mL of deionized water to form solution 1, so that the concentrations of lanthanum element and cobalt element in solution 1 are 1.2 mol / L and 0.84 mol / L, respectively, dissolving 0.5 g of chitosan in 2 mL of acetone to obtain solution 2, and then mixing solution 1 and solution 2 by stirring to obtain a coating solution;
[0057] S2, mixing 25g of lithium cobalt oxide positive electrode material matrix particles with the coating liquid by stirring, and then performing a hydrothermal reaction at 150°C for 6h, filtering the obtained hydrothermal reaction product, and vacuum drying it at 120°C for 6h to obtain an intermediate product;
[0058] S3. The intermediate product obtained in step S2 is calcined in an oxygen-containing atmosphere at 850° C. for 8 hours to obtain a lithium battery positive electrode material, which includes positive electrode material matrix particles and a composite metal oxide coating layer wrapped on the surface of the positive electrode material matrix particles.
[0059] From the XRD characterization results, it can be seen that the perovskite-type composite metal oxide LaCoO3 was successfully synthesized. From the EDS characterization, it can be seen that the lanthanum element and the cobalt element are evenly distributed on the surface of the lithium cobalt oxide positive electrode material, that is, LaCoO3 is evenly coated on the surface of the positive electrode material, wherein the content of LaCoO3 is 0.69wt%.
[0060] Example 3
[0061] S1, dissolving lanthanum acetate and nickel acetate in a molar ratio of lanthanum ions to nickel ions of 1:1.5 in 70 mL of deionized water to form solution 1, so that the concentrations of lanthanum and nickel in solution 1 are 0.8 mol / L and 1.2 mol / L, respectively, dissolving 0.1 g of chitosan in 2 mL of acetone to obtain solution 2, and then mixing solution 1 and solution 2 by stirring to obtain a coating solution;
[0062] S2, mixing 25g of lithium cobalt oxide positive electrode material matrix particles with the coating liquid by stirring, and then performing a hydrothermal reaction at 150°C for 20h, filtering the obtained hydrothermal reaction product, and vacuum drying it at 120°C for 6h to obtain an intermediate product;
[0063] S3. The intermediate product obtained in step S2 is calcined in an oxygen-containing atmosphere at 850° C. for 8 hours to obtain a lithium battery positive electrode material, which includes positive electrode material matrix particles and a composite metal oxide coating layer wrapped on the surface of the positive electrode material matrix particles.
[0064] From the XRD characterization results, it can be seen that the perovskite-type composite metal oxide LaNiO3 was successfully synthesized. From the EDS characterization, it can be seen that the lanthanum and nickel elements are evenly distributed on the surface of the lithium cobalt oxide positive electrode material, that is, LaNiO3 is evenly coated on the surface of the positive electrode material, wherein the content of LaNiO3 is 0.67wt%.
[0065] Example 4
[0066] A lithium battery positive electrode material is prepared according to the method of Example 1, except that the lithium cobalt oxide positive electrode material matrix particles are replaced by nickel-cobalt-manganese ternary positive electrode material matrix particles of the same mass, and other conditions are the same to obtain a lithium battery positive electrode material, which includes positive electrode material matrix particles and a composite metal oxide coating layer wrapped on the surface of the positive electrode material matrix particles.
[0067] From the XRD characterization results, it can be seen that the perovskite-type composite metal oxide LaCoO3 was successfully synthesized. From the EDS characterization, it can be seen that the lanthanum and cobalt elements are evenly distributed on the surface of the nickel-cobalt-manganese ternary positive electrode material, that is, LaNiO3 is evenly coated on the surface of the positive electrode material, among which the content of LaCoO3 is 0.72wt%.
[0068] Example 5
[0069] A lithium battery positive electrode material is prepared according to the method of Example 1, except that lanthanum chloride is replaced by the same molar amount of praseodymium chloride, and other conditions are the same to obtain a lithium battery positive electrode material, which includes positive electrode material matrix particles and a composite metal oxide coating layer wrapped on the surface of the positive electrode material matrix particles.
[0070] From the XRD characterization results, it can be seen that the perovskite-type composite metal oxide PrCoO3 was successfully synthesized. From the EDS characterization, it can be seen that the praseodymium element and the cobalt element are evenly distributed on the surface of the lithium cobalt oxide positive electrode material, that is, PrCoO3 is evenly coated on the surface of the positive electrode material, wherein the content of PrCoO3 is 0.75wt%.
[0071] Example 6
[0072] A lithium battery positive electrode material is prepared according to the method of Example 1, except that the same molar amount of gadolinium chloride is used instead of lanthanum chloride, and the other conditions are the same to obtain a lithium battery positive electrode material, which includes positive electrode material matrix particles and a composite metal oxide coating layer wrapped on the surface of the positive electrode material matrix particles.
[0073] From the XRD characterization results, it can be seen that the perovskite-type composite metal oxide GdCoO3 was successfully synthesized. From the EDS characterization, it can be seen that the gadolinium element and the cobalt element are evenly distributed on the surface of the lithium cobalt oxide positive electrode material, that is, GdCoO3 is evenly coated on the surface of the positive electrode material, wherein the content of GdCoO3 is 0.68wt%.
[0074] Example 7
[0075] A lithium battery positive electrode material is prepared according to the method of Example 1, except that terbium chloride is used instead of lanthanum chloride in the same molar amount, and other conditions are the same to obtain a lithium battery positive electrode material, which includes positive electrode material matrix particles and a composite metal oxide coating layer wrapped on the surface of the positive electrode material matrix particles.
[0076] From the XRD characterization results, it can be seen that the perovskite-type composite metal oxide TbCoO3 was successfully synthesized. From the EDS characterization, it can be seen that the terbium element and the cobalt element are evenly distributed on the surface of the lithium cobalt oxide positive electrode material, that is, TbCoO3 is evenly coated on the surface of the positive electrode material, wherein the content of TbCoO3 is 0.54wt%.
[0077] Example 8
[0078] A lithium battery positive electrode material is prepared according to the method of Example 1, except that yttrium chloride is used instead of lanthanum chloride in the same molar amount, and other conditions are the same to obtain a lithium battery positive electrode material, which includes positive electrode material matrix particles and a composite metal oxide coating layer wrapped on the surface of the positive electrode material matrix particles.
[0079] From the XRD characterization results, it can be seen that the perovskite-type composite metal oxide YCoO3 was successfully synthesized. From the EDS characterization, it can be seen that the yttrium element and the cobalt element are evenly distributed on the surface of the lithium cobalt oxide positive electrode material, that is, YCoO3 is evenly coated on the surface of the positive electrode material, wherein the content of YCoO3 is 0.50wt%.
[0080] Example 9
[0081] A lithium battery positive electrode material is prepared according to the method of Example 1, except that the same molar amount of titanium chloride is used instead of cobalt chloride, and other conditions are the same to obtain a lithium battery positive electrode material, which includes positive electrode material matrix particles and a composite metal oxide coating layer wrapped on the surface of the positive electrode material matrix particles.
[0082] From the XRD characterization results, it can be seen that the perovskite-type composite metal oxide LaTiO3 was successfully synthesized. From the EDS characterization, it can be seen that the lanthanum and titanium elements are evenly distributed on the surface of the lithium cobalt oxide positive electrode material, that is, LaTiO3 is evenly coated on the surface of the positive electrode material, wherein the content of LaTiO3 is 0.61wt%.
[0083] Example 10
[0084] A lithium battery positive electrode material is prepared according to the method of Example 1, except that the concentrations of lanthanum and cobalt in solution 1 are both 0.2 mol / L, the hydrothermal reaction temperature is 120°C, and the other conditions are the same to obtain a lithium battery positive electrode material, which includes positive electrode material matrix particles and a composite metal oxide coating layer wrapped on the surface of the positive electrode material matrix particles.
[0085] From the XRD characterization results, it can be seen that the perovskite-type composite metal oxide LaCoO3 was successfully synthesized. From the EDS characterization, it can be seen that the lanthanum element and the cobalt element are evenly distributed on the surface of the lithium cobalt oxide positive electrode material, that is, LaCoO3 is evenly coated on the surface of the positive electrode material, wherein the content of LaCoO3 is 0.13wt%.
[0086] Embodiment 11
[0087] A lithium battery positive electrode material is prepared according to the method of Example 1, except that the concentrations of lanthanum and cobalt in solution 1 are both 3 mol / L, the hydrothermal reaction temperature is 170°C, and the other conditions are the same to obtain a lithium battery positive electrode material, which includes positive electrode material matrix particles and a composite metal oxide coating layer wrapped on the surface of the positive electrode material matrix particles.
[0088] From the XRD characterization results, it can be seen that the perovskite-type composite metal oxide LaCoO3 was successfully synthesized. From the EDS characterization, it can be seen that the lanthanum element and the cobalt element are evenly distributed on the surface of the lithium cobalt oxide positive electrode material, that is, LaCoO3 is evenly coated on the surface of the positive electrode material, wherein the content of LaCoO3 is 1.93wt%.
[0089] Example 12
[0090] A lithium battery positive electrode material is prepared according to the method of Example 1, except that the same molar amount of calcium chloride is used instead of lanthanum chloride and the same molar amount of ferric chloride is used instead of cobalt chloride, and other conditions are the same to obtain a lithium battery positive electrode material, which includes positive electrode material matrix particles and a composite metal oxide coating layer wrapped on the surface of the positive electrode material matrix particles.
[0091] The XRD characterization results show that the perovskite-type composite metal oxide CaFeO3 was successfully synthesized. The EDS characterization shows that the calcium and iron elements are evenly distributed on the surface of the lithium cobalt oxide positive electrode material, that is, CaFeO3 is evenly coated on the surface of the positive electrode material, wherein the content of CaFeO3 is 0.68wt%.
[0092] Embodiment 13
[0093] A lithium battery positive electrode material is prepared according to the method of Example 1, except that the same molar amount of strontium chloride is used instead of lanthanum chloride and the same molar amount of manganese chloride is used instead of cobalt chloride, and other conditions are the same to obtain a lithium battery positive electrode material, which includes positive electrode material matrix particles and a composite metal oxide coating layer wrapped on the surface of the positive electrode material matrix particles.
[0094] From the XRD characterization results, it can be seen that the perovskite-type composite metal oxide SrMnO3 was successfully synthesized. From the EDS characterization, it can be seen that the strontium element and the manganese element are evenly distributed on the surface of the lithium cobalt oxide positive electrode material, that is, SrMnO3 is evenly coated on the surface of the positive electrode material, wherein the content of SrMnO3 is 0.64wt%.
[0095] Comparative Example 1
[0096] 200 g of lithium cobalt oxide positive electrode material matrix particles were added to 400 mL of deionized water, and then 40 g of lanthanum chloride, 40 g of cobalt chloride and 20 mL of 5% ethylene glycol were added. The mixture was stirred at 80 ° C for 24 h, and the material was dried in a vacuum oven at 120 ° C. Then, the material was calcined at 850 ° C for 8 h to obtain a reference lithium battery positive electrode material.
[0097] Comparative Example 2
[0098] 300 g of lithium cobalt oxide positive electrode material matrix particles, 40 g of lanthanum oxalate and 40 g of cobalt oxalate were mixed evenly in a ball mill, and then calcined at 850° C. for 8 h to obtain a reference lithium battery positive electrode material.
[0099] Comparative Example 3
[0100] A reference lithium battery positive electrode material was prepared according to the method of Example 1, except that lanthanum chloride was replaced by cobalt chloride in the same molar amount, and other conditions were the same, thus obtaining a reference lithium battery positive electrode material.
[0101] Comparative Example 4
[0102] A reference lithium battery positive electrode material was prepared according to the method of Example 1, except that cobalt chloride was replaced by lanthanum chloride in the same molar amount, and other conditions were the same, thus obtaining a reference lithium battery positive electrode material.
[0103] Test Case
[0104] The lithium battery positive electrode materials prepared in the above examples and comparative examples were tested for oxygen evolution overpotential, gram capacity, cycle performance, and gas production performance according to the following methods. The results are shown in Table 1.
[0105] (1) Oxygen evolution overpotential test method
[0106] A. Preparation of test electrodes: 7 mg of lithium battery positive electrode material was dispersed in a mixed solution of 0.8 mL of deionized water, 0.2 mL of isopropanol and 10 μL of Nafion solution. The volume ratio of deionized water, isopropanol and Nafion solution was 4:1:0.05. The mixture was ultrasonically treated for 40 min to uniformly disperse and obtain a good dispersion similar to ink. 5 μL of the dispersion was dropped on a glassy carbon electrode (Pine) with a diameter of 5 mm using a pipette. The catalyst loading was 0.354 mg cm -2 , and obtain the test electrode after natural drying;
[0107] B. The test electrode prepared above was charged at 100 mV·s -1 The activation was performed for 100 cycles at a scanning speed of 100 sccm. During the activation process, oxygen was continuously introduced at a flow rate of 100 sccm. When the cyclic voltammetry curve was stable, the test was performed. The parameters of the linear scanning voltammetry test were set as follows: electrode speed 1600 rpm, scanning speed 5 mV·s -1 , the recorded current density reached 10 mA cm -2 The overpotential at which η is generated is the oxygen evolution overpotential η. Each positive electrode material is tested three times and the average value of the three times is taken as the final η value.
[0108] (2) Gram capacity and cycle performance test method: The positive electrode materials obtained in the above embodiments and comparative examples were mixed with conductive carbon and flux PVDF in a weight ratio of 90:5:5 in NMP and coated on aluminum foil to obtain a pole piece; the pole piece was dried in a blast oven at 85°C and then placed in a vacuum oven at 130°C to dry overnight; the dried pole piece was rolled and used as a battery positive electrode (compacted density of 4.0 g / cm 3 ), lithium metal as the battery negative electrode, a single layer of polyethylene film as the separator, 1M LiPF6-EC-EMC (that is, the concentration of LiPF6 in EC-EMC solvent is 1M, where EC is ethylene carbonate, EMC is methyl ethyl carbonate, and the volume ratio of EC:EMC is 3:7) as the electrolyte, and the battery was assembled for electrochemical testing.
[0109] The battery was placed at 25°C, charged from 3.0V to 4.53V at a charging rate of 0.5C, and then discharged to 3.0V at a discharge rate of 0.5C. The discharge capacity this time was determined as the initial discharge capacity. The initial gram capacity was obtained by dividing the discharge capacity by the mass of the active substance (positive electrode material). The above charge and discharge cycle was repeated 50 times, and the discharge capacity of the 50th discharge was measured. The gram capacity after the cycle was obtained by dividing the discharge capacity by the mass of the active substance (positive electrode material). The cycle capacity retention rate = 50th gram capacity / initial gram capacity.
[0110] (3) Gas production performance test method: Use an in-situ gas volume monitor for testing.
[0111] Table 1
[0112]
[0113] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A low gas generation positive electrode material, characterized in that: The low gas generation positive electrode material comprises a positive electrode material matrix particle and a composite metal oxide coating layer wrapped on the surface of the positive electrode material matrix particle; the oxygen evolution overpotential of the lithium battery positive electrode material is ≤0.4V; the composite metal oxide in the composite metal oxide coating layer is a perovskite-type compound with a general chemical formula of ABO3, wherein the A element is a rare earth or alkaline earth metal element, and the B element is a transition metal element.
2. The low gas generation positive electrode material according to claim 1, characterized in that: The positive electrode material matrix particles are selected from at least one of lithium cobalt oxide positive electrode material matrix particles, lithium iron phosphate positive electrode material matrix particles, nickel cobalt manganese positive electrode material matrix particles and nickel cobalt aluminum positive electrode material matrix particles.
3. The low gas generation positive electrode material according to claim 1, characterized in that: Based on the total mass of the low gas generating positive electrode material, the content of the composite metal oxide ABO3 is 0.5-1.5wt%.
4. The method for preparing a low gas generating cathode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: subjecting the positive electrode material matrix particles to a hydrothermal reaction with a coating liquid containing an A element, a B element and chitosan, and then calcining the obtained hydrothermal reaction product in an oxygen-containing atmosphere to obtain a lithium battery positive electrode material.
5. The method for preparing a low gas generating cathode material according to claim 4, characterized in that: The coating liquid is prepared according to the following method: adding metal salt I containing element A and metal salt II containing element B into deionized water to form solution 1, mixing chitosan with an organic solvent to obtain solution 2, and then mixing solution 1 and solution 2 to obtain the coating liquid.
6. The method for preparing a low gas generating cathode material according to claim 5, characterized in that: The molar ratio of element A to element B in the solution 1 is 1:(0.5-1.5); Preferably, the concentration of element A in the solution 1 is 0.8 to 1.2 mol / L; Preferably, the concentration of element B in the solution 1 is 0.8 to 1.2 mol / L; Preferably, the concentration of chitosan in the solution 2 is 0.1 to 0.5 g / mL; Preferably, the volume ratio of solution 1 to solution 2 is (25-45):1; Preferably, the metal salt I and the metal salt II are each independently selected from at least one of sulfate, nitrate, acetate, oxalate and chloride.
7. The method for preparing a low gas generating cathode material according to claim 4, characterized in that: The element A is at least one of La, Pr, Gd, Tb, Ca, and Sr; The B element is at least one of Co, Mn, Fe and Ni.
8. The method for preparing a low gas generating cathode material according to claim 4, characterized in that: The temperature of the hydrothermal reaction is 110-170° C., and the time is 6-20 hours; the temperature of the calcination treatment is 700-1100° C., and the time is 4-12 hours.
9. A low gas generating positive electrode material prepared by the method according to any one of claims 4 to 8.
10. Use of the low gas generating cathode material according to any one of claims 1 to 3 and 9 in a lithium ion battery.
Citation Information
Cited By
Sodium-ion battery positive electrode material, preparation method, sodium-ion battery and electric equipment
CN119786557A
Sodium-ion battery cathode materials, preparation methods, sodium-ion batteries, and related electrical equipment
CN119786557B
Composite positive electrode material with sodium-oxygen permeable layer as well as preparation method and application of composite positive electrode material
CN121282142A
